2022
DOI: 10.3390/bios12121124
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Refractive Index Sensor Enhanced with Chitosan/Au Bilayer Thin Film for Dopamine Detection

Abstract: Surface plasmonic sensors have received considerable attention, found extensive applications, and outperformed conventional optical sensors. In this work, biopolymer chitosan (CS) was used to prepare the bilayer structure (CS/Au) of a plasmonic refractive index sensor for dopamine (DA) detection. The sensing characteristics of the developed plasmonic sensor were evaluated. Increasing DA concentrations significantly shifted the SPR dips. The sensor exhibited stability and a refractive index sensitivity of 8.850… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…For colorimetric method, analysis of colorless compounds is not possible and does not work in IR and UV regions [44] [45]. On the other hand, SPR sensors based on glass chips [29], [51] show better detection limits than these techniques. The proposed work utilizes optical fiber as a substrate which offers several advantages such as electromagnetic interference immunity and remote detection, which are not possible for glass chip-based sensors.…”
Section: ) Selectivity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…For colorimetric method, analysis of colorless compounds is not possible and does not work in IR and UV regions [44] [45]. On the other hand, SPR sensors based on glass chips [29], [51] show better detection limits than these techniques. The proposed work utilizes optical fiber as a substrate which offers several advantages such as electromagnetic interference immunity and remote detection, which are not possible for glass chip-based sensors.…”
Section: ) Selectivity Testmentioning
confidence: 99%
“…Recently, another SPR sensor was reported with a bilayer structure of chitosan and gold-film to sense dopamine [29].…”
Section: Introductionmentioning
confidence: 99%
“…One notable approach involves combining plasmonic nanoparticles with polymers, resulting in the development of plasmonic-polymer nanocomposites and hybrid plasmonic nanostructures [17][18][19][20]. The goal of this combination is to obtain novel materials and devices with enhanced functionality and responsiveness [21][22][23]. The synergistic effects of these hybrid nanostructured materials can be leveraged in functional systems, endowing them with remarkable optoelectronic, sensing, catalytic, and antibacterial properties, as well as improved light harvesting efficiency [17,18,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Nowadays, due to the advantages of fast response and precise real-time detection, a variety of optical RI sensors have been developed, which are widely used to monitor the tiny change of the chemical constituents (e.g., 10 −9 RIU, which corresponds to approximately 1 fmol/L of salt in water). [4][5][6] For example, Jian et al demonstrated the highly sensitive cell concentration detection by exploiting the resonant optical tunneling effect (ROTE), with a desirable sensitivity of 19 µm/RIU. [7] It is reported that the nano-dot enhanced plasmonic biosensor can detect the fractional changes of the electrolyte concentration and glucose concentration in human blood.…”
Section: Introductionmentioning
confidence: 99%